2020 Consensus of Taiwan Society of Cardiology on the pharmacological management of patients with type 2 diabetes and cardiovascular diseases. Issue 7 (29th May 2020) - Chiang, Chern-En; Ueng, Kwo-Chang; Chao, Ting-Hsing; Lin, Tsung-Hsien; Wu, Yih-Jer; Wang, Kang-Ling; Sung, Shih-Hsien; Yeh, Hung-I; Li, Yi-Heng; Liu, Ping-Yen; Chang, Kuan-Cheng; Shyu, Kou-Gi; et al.
Abstract : The global incidence and prevalence of type 2 diabetes have been escalating in recent decades. The total diabetic population is expected to increase from 415 million in 2015 to 642 million by 2040. Patients with type 2 diabetes have an increased risk of atherosclerotic cardiovascular disease (ASCVD). About two-thirds of patients with type 2 diabetes died of ASCVD. The association between hyperglycemia and elevated cardiovascular (CV) risk has been demonstrated in multiple cohort studies. However, clinical trials of intensive glucose reduction by conventional antidiabetic agents did not significantly reduce macrovascular outcomes. In December 2008, U.S. Food and Drug Administration issued a mandate that every new antidiabetic agent requires rigorous assessments of its CV safety. Thereafter, more than 200, 000 patients have been enrolled in a number of randomized controlled trials (RCTs). These trials were initially designed to prove noninferiority. It turned out that some of these trials demonstrated superiority of some new antidiabetic agents versus placebo in reducing CV endpoints, including macrovascular events, renal events, and heart failure. These results are important in clinical practice and also provide an opportunity for academic society to formulate treatment guidelines or consensus to provide specific recommendations for glucose control in various CV diseases. In 2018, the Taiwan Society of Cardiology (TSOC) and the Diabetes Association of Republic of China (DAROC) published the first joint consensus on the "Pharmacological Management of Patients with Type 2 Diabetes and Cardiovascular Diseases." In 2020, TSOC appointed a new consensus group to revise the previous version. The updated 2020 consensus was comprised of 5 major parts: (1) treatment of diabetes in patients with multiple risk factors, (2) treatment of diabetes in patients with coronary heart disease, (3) treatment of diabetes in patients with stage 3 chronic kidney disease, (4) treatment of diabetes in patients with a history of stroke, and (5) treatment of diabetes in patients with heart failure. The members of the consensus group thoroughly reviewed all the evidence, mainly RCTs, and also included meta-analyses and real-world evidence. The treatment targets of HbA1c were finalized. The antidiabetic agents were ranked according to their clinical evidence. The consensus is not mandatory. The final decision may need to be individualized and based on clinicians' discretion.